L’ETICA DELLA DISILLUSIONE: LA LEZIONE DEI MORALISTI IN CIORAN (Analele Universității București. Limba și literatură română, 2025)
Emil Cioran’s work is marked by a tension between classical moralism and a radical questioning of subjective identity. This article explores the relationship between Cioran and the tradition of French moralists, from La Rochefoucauld and Chamfort to Joubert, highlighting their decisive role in shaping his writing and intellectual transformation. The transition from Romanian to French was not merely a stylistic exercise for Cioran but a true form of exile—a self-effacement that enabled him to develop a new ethical framework. Through an analysis of his statements and critical reception, this study demonstrates how Cioran, while adopting the formal rigor andpsychological acuity of the moralists, ultimately forged an ethics of disillusionment that sets him apart from the tradition he inherited. Central to this reflection is his encounter with Benjamin Fondane, a tragic and pivotal figure in his intellectual journey, marking the final renunciation of ideological remnants and the embrace of a writing practice grounded in uprootedness and the suspension of judgment.